An application of dynamic thermal line rating control system to up-rate the ampacity of overhead transmission lines - Kim, S. D.; Morcos, Medhat M. (My University, 2013)
A method is proposed to utilize dynamic line rating (DLR) system on old transmission lines to up-rate ampacity without replacing old conductors or increasing line voltage. A DLR system applicable to double-circuit transmission lines is designed based on maximum allowable conductor temperature, conductor temperature at limit-dip (sag) margin, and transformer maximum load. The improved performance of the system is reported.
Keywords: Ampacity; Dynamic line rating; Overhead lines